The impact of the Covid pandemic on the injury rate at Europe's top level judo tournaments - Smolders, P. (The Arts and Sciences of Judo, 2023)
Since 2005 the EJU Medical Commission has collected data on injuries happening during top-level events all over Europe. Results were published in a previous edition of this joumal. When in early 2020 our judo lives came to an abrupt halt with different kinds of lockdowns in all the countries of Europe, we were very concerned about what this would mean in terms of training possibilities, preventative exercises and potentially an increase in the number of injuries. In Europe the EJU Anti-Covid Taskforce worked tirelessly to try to restart all judo events. With the help of the IJF Covid Protocol, slowly but surely, we were on the right track. Extensive testing, creation of 'judo bubbles,' isolation and quarantine, helped the judo world back to its feet. Tournaments and training camps came back but our major concern remained: were our judoka well enough prepared for top-level events or would all this result in an increased injury rate?